The Automated Trip Alert System for Earth Leakage Circuit Breaker (ELCB) - Nasurdin, Nur Muhammad Asyraf; Bohari, Azuwien Aida (Progress in Engineering Application and Technology, 2023)
The automatic system is the most used method to facilitate tasks that require human effort. This method is typically employed in systems that necessitate immediate action in the event of any issues, ensuring prompt resolution. However, the widespread adoption of this system has been limited due to human resources constraints and high maintenance costs. Based on the Internet of Things (IoT) approach, this project presents a suitable design for an automatic system that can be installed in residential areas. This system assists in maintaining home security during the absence of occupants. The project produces a monitoring system that operates in real-time using an application platform and the Internet of Things (IoT). By utilizing voltage sensors, the voltage readings can be accessed by homeowners even when away from home. Additionally, this project ensures the safety of electrical appliances that require continuous electrical connection. In the event of a circuit malfunction in the house, the time required to detect the fault is significantly reduced, enabling users to be promptly informed. The project's outcome demonstrates the successful detection and reactivation of the Earth Leakage Circuit Breaker (ELCB) in the event of a short circuit. Overall, this project enhances the Distribution Box (DB) system by effectively reactivating the ELCB.